2021
DOI: 10.1002/pd.6052
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular outflow tract abnormalities in monochorionic twin pregnancies without twin‐to‐twin transfusion syndrome: Prenatal course and postnatal long‐term outcomes

Abstract: Objectives Right ventricular outflow tract abnormalities (RVOTA) have been mostly reported in recipient twins (RT) of monochorionic/diamniotic (MC/DA) twin pregnancies with twin‐to‐twin transfusion syndrome (TTTS). Aim of the study was to describe RVOTA detected in MC/DA pregnancies without TTTS. Methods Cases of RVOTA were retrieved from our database among all MC/DA pregnancies without TTTS from 2009 to 2018. Results Out of 891 MC/DA twin pregnancies without TTTS, 14 (1.6%) were associated with RVOTA: 10 pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 31 publications
2
13
2
Order By: Relevance
“…fPA was defined as retrograde flow across the pulmonary valve (PV) in systole with absent or minimal forward PV flow, together with the presence of reverse flow in the ductus arteriosus 3 . PS was defined as turbulent flow across the PV with an increased peak systolic velocity of the pulmonary artery (greater than 1 m/s) with or without the presence of thickened and domed pulmonary valve cusps associated with structural or functional right heart abnormalities 6,7,34 . PA was defined as an anatomical pulmonary valve anomaly without antegrade flow across the RVOT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…fPA was defined as retrograde flow across the pulmonary valve (PV) in systole with absent or minimal forward PV flow, together with the presence of reverse flow in the ductus arteriosus 3 . PS was defined as turbulent flow across the PV with an increased peak systolic velocity of the pulmonary artery (greater than 1 m/s) with or without the presence of thickened and domed pulmonary valve cusps associated with structural or functional right heart abnormalities 6,7,34 . PA was defined as an anatomical pulmonary valve anomaly without antegrade flow across the RVOT.…”
Section: Methodsmentioning
confidence: 99%
“…In monochorionic (MC) twins, right ventricular outflow tract (RVOT) abnormalities including pulmonary stenosis (PS) and functional pulmonary atresia (fPA) are serious cardiac complications for recipient twins complicated with twin–twin transfusion syndrome (TTTS); these RVOT abnormalities are found in approximately 8%–21% of recipient twins prenatally 1–6 . An RVOT abnormality has also been reported in MC twins affected by other complications, such as selective intrauterine growth restriction (sIUGR) and twin anemia‐polycythemia sequence (TAPS) 7,8 . Fetoscopic laser photocoagulation (FLP), which is the treatment option for TTTS, TAPS, and sIUGR, disrupts the adverse feto‐fetal hemodynamic communications 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the cardiac function changes observed in sIUGR, explain why Faiola et al. found, in a cohort of almost 900 monochorionic twins pregnancies, the risk of right ventricular outflow tract obstruction is increased (incidence of up to 1.6%), even in the absence of TTTS 12 …”
Section: Fetal Cardiovascular Function In Monochorionic Twinsmentioning
confidence: 99%
“…Indeed, the cardiac function changes observed in sIUGR, explain why Faiola et al found, in a cohort of almost 900 monochorionic twins pregnancies, the risk of right ventricular outflow tract obstruction is increased (incidence of up to 1.6%), even in the absence of TTTS. 12 A critical requirement, however, before implementing routine cardiac function measurements in research or clinical practice, is the availability of reliable normal values for uncomplicated monochorionic twins. Here Torres presents such nomograms, derived from a cohort of 55 prospectively followed uncomplicated monochorionic twin pregnancies undergoing longitudinal measurements.…”
Section: Fetal Cardiovascular Function In Monochorionic Twinsmentioning
confidence: 99%
“…A strength of this study is the examination of a large cohort of cases throughout years, with the same method reported in a non-TTTS population, as previously reported by our group 16 . The results of the present study further contribute to the acquisition of knowledge on the prevalence of cardiac abnormalities, in particular right ventricle outflow tract obstructions, in different MC twin pregnancies, both complicated and not complicated by TTTS, with focus on the treatment received for this condition.…”
Section: Strengths and Limitationsmentioning
confidence: 99%